Card game method to improve the number of counting operations of elementary school students in Buru District - M. Yusran Zakaria; Irma Maghfirah; Nur Fadhilah Amir; Taufik Taufik (Universitas Sembilanbelas November Kolaka, 2020)
This research aims to describe the counting operation capabilities of grade II elementary school students with card game methods. This type of research is classroom action research with Kemmis and Mc Taggart models. The research was conducted at public elementary school (Sekolah Dasar Negeri or “SDN”) 1 Teluk Kaiely, SDN 1 Lilialy, and SDN 3 Namlea. Data is collected with tests and observations. Furthermore, the data is analyzed with qualitative and quantitative techniques. The results showed that by using the card game method, the ability to calculate the grade II elementary school students improved from the beginning of the pre-cycle to cycle II. The average value in pre-cycle is 65 with the percentage of 42%. The average value increases to 66, with a percentage of 58%. The average score increased to 78 with the percentage of 81% reach the cut of score in cycle II